Representasi Profesionalisme Pegawai Bank Rakyat Indonesia (BRI) Melalui Web Series Pakai Hati Dalam Meningkatkan Citra - Muhammad Ilham Dikostariza; Muhammad Al Assad Rohimakumullah (Universitas Telkom, 2024)
Content in the form of web series is a relatively new image enhancement strategy through social media by several companies. BRI produces web series content with the aim of enhancing its image. However, it is not only BRI’s image that isdisplayed in the web series. As for the meaning of professionalism that is raised to be one of the attractions of the BRIweb series, in this study professionalism refers to Law Number 5 of 2014 concerning the State Civil Apparatus (ASN). Thisresearch is interesting because webseries content is something new, and BRI uses the webseries to show their professionalism working at BRI. The research will discuss the representation of the professionalism of BRI bank employees throughwebseries with a heart in enhancing image, using qualitative methods and integrating semiotic theory from Roland Barthes,and the data collection technique used in this research is in the form of observation. in the webseries they carry out acts ofprofessionalism, the results of this study show that this webseries is true, most of it shows professionalism referring to LawNumber 5 of 2014 which aims to improve image.